AMP-Activated Protein Kinase (AMPK) Regulates Energy Metabolism through Modulating Thermogenesis in Adipose Tissue - Wu, Lingyan; Zhang, Lina; Li, Bohan; Jiang, Haowen; Duan, Yanan; Xie, Zhifu; Shuai, Lin; Li, Jia; Li, Jingya (Frontiers in Physiology, 2018)
Obesity occurs when excess energy accumulates in white adipose tissue (WAT), whereas brown adipose tissue (BAT), which is specialized in dissipating energy through thermogenesis, potently counteracts obesity. White adipocytes can be converted to thermogenic “brown-like” cells (beige cells; WAT browning) under various stimuli, such as cold exposure. AMP-activated protein kinase (AMPK) is a crucial energy sensor that regulates energy metabolism in multiple tissues. However, the role of AMPK in adipose tissue function, especially in the WAT browning process, is not fully understood. To illuminate the effect of adipocyte AMPK on energy metabolism, we generated Adiponectin-Cre-driven adipose tissue-specific AMPK α1/α2 KO mice (AKO). These AKO mice were cold intolerant and their inguinal WAT displayed impaired mitochondrial integrity and biogenesis, and reduced expression of thermogenic markers upon cold exposure. High-fat-diet (HFD)-fed AKO mice exhibited increased adiposity and exacerbated hepatic steatosis and fibrosis and impaired glucose tolerance and insulin sensitivity. Meanwhile, energy expenditure and oxygen consumption were markedly decreased in the AKO mice both in basal conditions and after stimulation with a β3-adrenergic receptor agonist, CL 316,243. In contrast, we found that in HFD-fed obese mouse model, chronic AMPK activation by A-769662 protected against obesity and related metabolic dysfunction. A-769662 alleviated HFD-induced glucose intolerance and reduced body weight gain and WAT expansion. Notably, A-769662 increased energy expenditure and cold tolerance in HFD-fed mice. A-769662 treatment also induced the browning process in the inguinal fat depots of HFD-fed mice. Likewise, A-769662 enhanced thermogenesis and oxygen consumption in differentiated inguinal stromal vascular fraction (SVF) cells. In summary, a lack of adipocyte AMPKα induced thermogenic impairment and obesity in response to cold and nutrient-overload, respectively, whereas chronic AMPK activation by A-769662 promoted WAT browning in inguinal WAT and protected against HFD-induced obesity and related metabolic dysfunction. These findings reveal a vital role for adipocyte AMPK in regulating the browning process in inguinal WAT and in maintaining energy homeostasis, which suggests that the targeted activation of adipocyte AMPK may be a promising strategy for anti-obesity therapy.